Floristic study of the Huehuetoca region, State of Mexico - Romero Rangel, Silvia; Rojas Zenteno, E. Carlos (Instituto de Ecología, A.C., 1991)
The pteridophyte and angiosperm flora of the Huehuetoca region, small (ca. 100 km2) area located on the Neovolcanic Belt in the northwest corner of the Valley of Mexico (states of Hidalgo and Mexico) and characterized by grassland, xerophytic scrub and oakscrub in a lacustrine plain (2250 m) interspersed with mountains (to 2650 m), is comprised of 579 species, in 83 families and 327 genera. Three of these species proved to be new to science (Asclepias nummularioides, A. rzedowskii, Bacchars erosoricola) and 19 species represent first record for the Valley of Mexico.